Allopregnanolone potentiates bioenergetic capacity and mitochondrial biogenesis in astrocytes. (December 2021) - Wang, Tian; Chen, Shuhua; Mao, Zisu; Shang, Yuan; Brinton, Roberta Diaz
Abstract: Background: We reported previously that the neurosteroid allopregnanolone (Allo) promotes neural stem cell regeneration and differentiation, reverses neurogenic, metabolic and cognitive deficits and reduces Alzheimer's disease (AD) pathology in a mouse model of AD. To further investigate the cell‐type specific mechanisms of Allo in regulating brain energy metabolism, we assessed the effect of Allo on mitochondrial bioenergetic profile and biogenesis in rat hippocampal astrocytes. Method: E18 rat hippocampal astrocyte were cultured for 10 days in DMEM:F12(1:1) with 10% FBS and then starved in 10% Charcoal stripped‐FBS / DMEM:F12 for 24 hours before treatment with 100nM Allo or 0.001% Vehicle overnight. Upon completion of treatment, cells were subject to morphological, biochemical, metabolic and transcriptomic characterization of their mitochondrial phenotypes. Result: In primary hippocampal astrocytes, Allo significantly attenuates serum deprivation‐induced bioenergetic deficits and oxidative stress by enhancing mitochondrial biogenesis and rebalancing mitochondrial dynamics. Allo treatment significantly enhances astrocytic mitochondrial biogenesis via Nrf1/Tfam signaling and reverses mitochondrial hyperfusion by elevating the ratio of mitochondrial fission protein Drp1 to the fusion protein Opa1. Functionally, Allo‐induced improvement in bioenergetic function is coupled with reduced inflammasome activation in astrocytes. Conclusion: Outcomes of our findings further support the promising therapeutic effects of Allo against bioenergetic deficits that emerge in early phases of AD, with mitochondria being a major effector.